Representations: material and immaterial modes of communication in the Bronze Age Aegean - Bennet, John (Sheffield studies in Aegean archaeology, 2021)
This volume presents a series of reflections on modes of communication in the Bronze Age Aegean, drawing on papers presented at two round table workshops of the Sheffield Centre for Aegean Archaeology on 'Technologies of Representation? and ?Writing and Non-Writing in the Bronze Age Aegean'. Each was designed to capture current developments in these interrelated research areas and also to help elide boundaries between ?science-based? and ?humanities-based? approaches, and between those focused on written communication (especially its content) and those interested in broader modes of communication. Contributions are arranged thematically in three groups: the first concerns primarily non-written communication, the second mainly written communication, and the third blurs this somewhat arbitrary distinction